Implications of TRPM3 and TRPM8 for sensory neuron sensitisation - Behrendt, Marc (Biological chemistry, 2024)
Sensory neurons serve to receive and transmit a wide range of information about the conditions of the world around us as well as the external and internal state of our body. Sensitisation of these nerve cells, i.e. becoming more sensitive to stimuli or the emergence or intensification of spontaneous activity, for example in the context of inflammation or nerve injury, can lead to chronic diseases such as neuropathic pain. For many of these disorders there are only very limited treatment options and in order to find and establish new therapeutic approaches, research into the exact causes of sensitisation with the elucidation of the underlying mechanisms and the identification of the molecular components is therefore essential. These components include plasma membrane receptors and ion channels that are involved in signal reception and transmission. Members of the transient receptor potential (TRP) channel family are also expressed in sensory neurons and some of them play a crucial role in temperature perception. This review article focuses on the heat-sensitive TRPM3 and the cold-sensitive TRPM8 (and TRPA1) channels and their importance in sensitisation of dorsal root ganglion sensory neurons is discussed based on studies related to inflammation and injury- as well as chemotherapy-induced neuropathy.
Gesehen am 07.01.2025